2018
DOI: 10.1111/ijac.13151
|View full text |Cite
|
Sign up to set email alerts
|

Dry‐sliding wear behavior of 3Y‐TZP/Al2O3‐NbC nanocomposites produced by conventional sintering and spark plasma sintering

Abstract: This work presents the initial results of the dry‐sliding wear behavior of 3 mol% yttria‐stabilized zirconia reinforced with 5 vol% alumina‐niobium carbide (3Y‐TZP/5 vol% Al2O3‐NbC) nanocomposites sintered by conventional sintering and spark plasma sintering methods in the temperature range of 1350‐1450°C. The reinforcement of 3Y‐TZP matrix with hard nanoparticles aimed to improve wear strength of the composites. Wear tests were performed by the ball‐on‐disc method using alumina (Al2O3) and tungsten carbide wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Moreover, the addition of nano‐powders has also attracted much attention for great potentiality in enhancing the mechanical performance of structural materials because of their high specific surface area and small grain size . It was reported that the dry‐sliding wear behavior against tungsten carbide cermet balls with 6 wt% cobalt (WC‐6%Co) of 3 mol% yttria‐stabilized zirconia reinforced by 5 vol% alumina‐niobium carbide hard nanoparticles would be significantly improved together with much enhanced mechanical strength . With 8.6 wt% (6.6 wt% TiC and 2 wt% TiN) nano‐powder, the transverse rupture strength of the prepared TiCN cermets through a liquid sintering method can be improved from 1831.6 to 2884.7 MPa without reducing its rigidity .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the addition of nano‐powders has also attracted much attention for great potentiality in enhancing the mechanical performance of structural materials because of their high specific surface area and small grain size . It was reported that the dry‐sliding wear behavior against tungsten carbide cermet balls with 6 wt% cobalt (WC‐6%Co) of 3 mol% yttria‐stabilized zirconia reinforced by 5 vol% alumina‐niobium carbide hard nanoparticles would be significantly improved together with much enhanced mechanical strength . With 8.6 wt% (6.6 wt% TiC and 2 wt% TiN) nano‐powder, the transverse rupture strength of the prepared TiCN cermets through a liquid sintering method can be improved from 1831.6 to 2884.7 MPa without reducing its rigidity .…”
Section: Introductionmentioning
confidence: 99%